Equality of opportunity in education: the spanish results in PISA 2012 - Antonio Villar (ADIDE Federación, 2014)
This article deals with the equality of opportunity of the Spanish educational system, according to the results of the PISA 2012. The key element is the analysis of the dependence of the students' outcomes, in the field of mathematics, and their family environment. The students' outcomes are expressed in terms of levels of competence whereas the family environment is measured by the Index of Socio-Economic and Cultural Status. We study the equality of opportunity observed in the different autonomous regions for which there are available data.  The main findings are: (i) There are relevant differences in the equality of opportunity of the Spanish regional educational systems; and (ii) The higher the average students' performance, the higher the equality of opportunity.